Influence of the tannic and gallic acids on stability of betacyanins from red beetroot (Beta vulgaris L.) crude extract. INFLUÊNCIA DOS ÁCIDOS TÂNICO E GÁLICO NA ESTABILIDADE DE BETACIANINAS DO EXTRATO BRUTO DE BETERRABA VERMELHA (Beta vulgaris L.) - D. A. DRUNKLER (Alimentos e Nutrição, 2008)
The use of e natural colorants in the food industry is limited because to its low stability under preparation, processing and storage conditions. Techniques for natural colorant’s stabilization, such as copigmentation, have been used frequently in scientific researches. The betacyanins that belong to the groups of the betalain presents in the red beetroot and are used as colorant in food. Tannic and gallic acids were used in this study as a copigment of betacyanin crude extract from red beetroot (Beta vulgaris L.). Betacyanin stability was investigated with and without tannic and gallic acid under different storage conditions in 70% ethanol extract: concentrations of 0.925g/100mL and 0.462g/100mL, pH values 5.00±0.05 and 6.80±0.05 at temperature of 25±1ºC, in the dark and in the presence of oxygen. Results revealed that pH and tannic and gallic acid addition (p<0.05) increased significantly the betacyanins half-life time. The tannic and gallic acids provided significant increase in stability of the betacyanins pigments at both concentrations evaluated, at pH value of 5.00 ± 0.05, tannic acid being more effective. O uso dos corantes naturais na indústria alimentícia é limitado em função de sua baixa estabilidade frente às condições de preparação, processamento e estocagem. Técnicas de estabilização de corantes naturais, tais como a copigmentação, vem encontrando destaque em pesquisas científicas. As betacianinas (coloração vermelha violeta), pertencentes ao grupo de pigmentos naturais denominados betalaínas, são as que predominam na beterraba vermelha (Beta vulgaris L.), sendo utilizadas como corante em alimentos. O objetivo do presente trabalho foi avaliar a estabilidade de betacianinas em extrato de beterraba (Beta vulgaris L.) etanólico a 70% adicionadas dos ácidos orgânicos tânico e gálico, nas concentrações de 0,462g/100mL e 0,925g/100mL, nos valores de pH de 5,00±0,05 e 6,80±0,05, temperatura de 25,0±1,0ºC, ausência de luz e em presença de oxigênio. Os resultados revelaram que o valor de pH e a adição dos ácidos orgânicos influenciaram significativamente (p<0,05) na estabilidade das betacianinas. O ácido tânico e o ácido gálico promoveram aumento significativo da estabilidade da cor do pigmento betacianina em pH de 5,00±0,05 sendo que o ácido tânico apresentou maior efeito protetor.